AB1385 Observational study of musculoskeletal problems in patients presenting to general medical clinics in urban slum setting in new delhi. (23rd January 2014) - Srirangan, S.; Nair, B.; Dolan, L.
Abstract : Background: Musculoskeletal problems are a leading cause for long term pain and physical disability affecting millions of people all over the world thereby presenting a significant health burden on the society.Musculoskeletal disorders can have significant negative impact on the individual and the family especially if the affected individual is the sole earning member- a scenario quite common in the urban slum setting. If musculoskeletal disorders are not recognized and treated in time it can lead to significant loss of earnings and diminish the working life of an individual. Objectives: The objective of the study was to observe the musculoskeletal burden amongst patients presenting to 3 general medical clinics which were conducted in an urban slum setting. Methods: This study was carried out by a team visiting three general medical clinics conducted under the auspices of Asha which is a health and developmental charity involved in providing medical services to the urban slum dwellers. 127 patients were evaluated over three days. A diagnosis of musculoskeletal problem was made by the Rheumatologist. A Black Osteoporosis score was calculated in a subgroup of women.Conditions were treated wherever possible in the clinic or patient referred to the nearest government hospital. Results: 19.7% of patients attending the clinic were male and 80.3% female. Nearly 40% (51 patients) of the 127 patients who attended the clinic had some musculoskeletal problem. Only 7 of the 51 patients (13.7%) had ever seen a medical practitioner for their musculoskeletal complaints. Of the 16 patients (4 male, 12 females) presenting with polyarthralgia; 5(31.2%) had inflammatory arthritis and 6(37.5%) gave a history of having contracted Chickungunya (arbovirus transmitted by mosquitoes) immediately preceding the onset of joint symptoms. There was overwhelming female preponderance amongst patients suffering from osteoarthritis. Over 70 percent of the 14 patients presenting with mechanical low back pain were women between 26-60 years of age and this subgroup was very flexible. Majority of them could flex to their ankles and had an SLR of 90 degrees. Majority could do leg stands greater than 5 minutes and could sit from a lying position and stand from a sitting position without using their arms. Black osteoporosis score was performed in 23 women. None had suffered low trauma fracture. 4 could not stand from sitting unaided. 4 had Black score =4, only 1 had score >5 implying high fracture risk. In total 8 procedures were carried out including soft tissue and intra articular steroid injections. Conclusions: A significant proportion of patients in this urban slum population attending general medical clinics had musculoskeletal problems. Mechanical back and knee pain are common in this population and majority of those patients assessed with mechanical back pain were found to be flexible. Amongst those assessed for osteoporosis- risk was found to be low. In a subgroup of patients with polyarthralgia history of contracting Chikungunya prior to onset of articular symptoms was noted. A systematic population study is required to assess the true prevalence of musculoskeletal problems within urban slums to facilitate health planning and allocation of adequate health resources to this otherwise vulnerable section of the society. Disclosure of Interest: None Declared